Case Report: Migrainous Infarct without Aura - Kamesh Gupta; Anurag Rohatgi; Shivani Handa (Case Reports in Neurology, 2017)
Background: Stroke in a migraine with aura has been documented in several cases, even deserving the merit of a classification as complicated migraine. Herein, we present a rare case of migrainous infarct without aura. The diagnosis was challenging due to lack of risk factors. The patient was unique in not having any other comorbidities. Case Presentation: The case is of a 21-year-old female presenting with right-sided hemiplegia and facial drooping. She had had an index presentation of throbbing headaches for the past 2 years, typical of a migraine but not preceded by any aura symptoms. However, in the current episode, the pain became excessively severe and accompanied by right-sided hemiplegia and facial drooping. A full investigation workup using MRI revealed evidence of infarct in the left temporoparietal and basal ganglion region. Conclusion: Our case highlights the need to evaluate silent ischemic stroke in case of prolonged headache with a history of migraine as well as the need for precaution to avoid the use of triptans or opioids in such a case. It also highlights the conditions that need to be excluded before labeling it as a migrainous infarct.